2007
DOI: 10.1097/hjr.0b013e32828622f9
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and the elderly

Abstract: Functional ageing processes are characterized by a loss of performance capabilities regarding coordination, flexibility, strength, speed, and endurance. The effects of ageing processes on the cardiovascular system and skeletal muscle are the foci of attention. After age 30, the maximum aerobic dynamic performance capacity decreases by an average of 8% per decade. The causes are mainly a reduction in the maximum cardiac output and decreases in capillarization and in the skeletal muscle mass. An improvement in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
60
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(67 citation statements)
references
References 127 publications
1
60
0
6
Order By: Relevance
“…Most sporting activities, e.g., swimming, ball games, or cycling, combine endurance, strength, balance, and flexibility training. Cross-sectional and interventional studies support that all those basic motor skills increase by regular training even in very old people and in elderly patients with chronic diseases [15,21,22,24,28]. Sporting activities may thus contribute toward meeting the physical activity recommendations.…”
Section: Introductionmentioning
confidence: 97%
“…Most sporting activities, e.g., swimming, ball games, or cycling, combine endurance, strength, balance, and flexibility training. Cross-sectional and interventional studies support that all those basic motor skills increase by regular training even in very old people and in elderly patients with chronic diseases [15,21,22,24,28]. Sporting activities may thus contribute toward meeting the physical activity recommendations.…”
Section: Introductionmentioning
confidence: 97%
“…Third, there is confirmation from neuroscience that physical activity has a strong impact on the brain structure of older adults (Hollman, Struder, Tagarakis, & King, 2007). According to Kramer and Erickson (2007a), randomized clinical trials involving older adults have already shown that physical training can change the brain structure, increasing gray matter in 355 the frontal and temporal cortex and anterior white matter (Colcombe et al, 2006) or increasing the cerebral blood volume (Pereira et al, 2006).…”
mentioning
confidence: 99%
“…On the other hand athletes lead a physically active life as their academic curriculum itself includes daily physical exercise and outdoor games (Choudhary et al, 2015). It has been documented physical inactivity as a major health problem (Blair, 2009) and regular exercise is important for health and well being (Wilt et al, 2004;Hollmann et al, 2007;Sattelmair et al, 2009). Physical inactivity is contributing factor in several chronic diseases and conditions (Vona et al, 2004;Hambrecht et al, 2000).…”
Section: Introductionmentioning
confidence: 99%